PENINGKATAN HASIL BELAJAR K3LH MELALUI PEMBERIAN KUIS PEMBELAJARAN PADA SISWA KELAS X SMK NEGERI 1 MARE KABUPATEN BONE - Riska Rahmayana; Kadirman Kadirman; Purnamawati Purnamawati (Universitas Negeri Makassar, 2017)
This reseacrh is a classroom action research which aims to improve the learning outcomes of students. The aims of this research is; (1) to know the activity in learning of K3LH throught giving the quiz (2) to know the results of K3LH learning after applied the method of giving the quiz (3) to know the influence of giving the quiz to the results of K3LH learning. The subject of this reseach consists of 34 students. The techniques of collection data using observation and giving test at the end of the cycle that related to materials on teaching. Research procedures consist of: (a) planning, (b) implementation, (c)observation and (d) reflection. The data collected will be analyzed by qualitative descriptive data analysis. Based on the results of the research, it can be conclud that through giving the quiz can improve the result of students learning. That is 50% increase to 82,36% with Minimum Completeness Criterion (KKM) that is 70